Optimization of main fermentation of high-gravity wort - Kosiv, Ruslana; Kharandiuk, Tetiana; Polyuzhyn, Lyubov; Palianytsia, Liubov; Berezovska, Natalia (Publishing House of Lviv Polytechnic National University, 2016)
The mathematical model has been developed to calculate the content of higher alcohols and esters depending on wort initial concentration and fermentation temperature. The process was optimized in accordance with the developed model. To obtain high-quality beer via high-gravity brewing technology the wort concentration was found to be 14–15 % relative to dry matter and main fermentation temperature of 284–285 K. Створено математичну модель, яка дає можливість розрахувати вміст вищих спиртів та естерів залежно від початкової концентрації сусла та температури бродіння. За рівняннями математичної моделі здійснено оптимізацію процесу. Встановлено, що для одержання пива високої якості за технологією високогустинного пивоваріння концентрація сусла повинна становити 14–15% сухих речовин, а температура головного бродіння 284–285 К.
Оптимізація головного бродіння високогустинного пивного сусла
Keywords: high-gravity brewing; fermentation byproducts; optimization; високогустинне пивоваріння; побічні продукти бродіння; оптимізація